2008
DOI: 10.1096/fj.08-109033
|View full text |Cite
|
Sign up to set email alerts
|

A soluble form of the receptor for advanced glycation endproducts (RAGE) is produced by proteolytic cleavage of the membrane‐bound form by the sheddase a disintegrin and metalloprotease 10 (ADAM10)

Abstract: The receptor for advanced glycation endproducts (RAGE) mediates responses to cell danger and stress. When bound by its many ligands (which include advanced glycation endproducts, certain members of the S100/calgranulin family, extracellular high-mobility group box 1, the integrin Mac-1, amyloid beta-peptide and fibrils), RAGE activates programs responsible for acute and chronic inflammation. RAGE is therefore also involved in cancer progression, diabetes, atherosclerosis, and Alzheimer's disease. RAGE has seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
429
6
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(472 citation statements)
references
References 37 publications
15
429
6
4
Order By: Relevance
“…Although other studies have shown that exogenous H 2 O 2 -induced activation of the transcriptional factors HSF (heat-shock transcription factor) (13) and STAT (signal transducer and activator of transcription) (3), which are powerful multifaceted modifiers of carcinogenesis, we do not yet know whether these factors regulate the expression of RAGE under oxidative stress in pancreatic tumors. Moreover, RAGE has several isoforms deriving from alternative splicing, including a soluble form called endogenous secretory RAGE (esRAGE) that acts as a decoy receptor (31). Additionally, there are several reports of cell membrane receptor protein ectodomain shedding (tumor necrosis factor receptor, betacellulin, calcineurin and RAGE) in response to stress (33,50).…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies have shown that exogenous H 2 O 2 -induced activation of the transcriptional factors HSF (heat-shock transcription factor) (13) and STAT (signal transducer and activator of transcription) (3), which are powerful multifaceted modifiers of carcinogenesis, we do not yet know whether these factors regulate the expression of RAGE under oxidative stress in pancreatic tumors. Moreover, RAGE has several isoforms deriving from alternative splicing, including a soluble form called endogenous secretory RAGE (esRAGE) that acts as a decoy receptor (31). Additionally, there are several reports of cell membrane receptor protein ectodomain shedding (tumor necrosis factor receptor, betacellulin, calcineurin and RAGE) in response to stress (33,50).…”
Section: Discussionmentioning
confidence: 99%
“…This proteolytic generation of sRAGE was initially described as occurring in mice 103 . Recent studies suggest that ADAM10 and MMP9 to be involved in RAGE shedding 13,14 . ADAM is known as a shedase to shed several inflammatory receptors and can be involved in regulation of RAGE/sRAGE balance.…”
Section: Soluble Rage Generated By Sheddingmentioning
confidence: 99%
“…7,8 Up to now we know that there are a number of distinct splice variants of sRAGE. 7 Therefore, it has been suggested that esRAGE might constitute only a part, but not all of the human sRAGE in plasma.…”
Section: Introductionmentioning
confidence: 99%